Analisis Problematika Pembelajaran Bahasa Indonesia di Madrasah Ibtidaiyah - Putri, Candra Avista; Uyun, Fitratul; Alimudin, Risky (IBTIDA', 2024)
The purpose of this research includes two main aspects, namely: 1) to improve students' ability and creativity in telling pictures using their own language. 2) to explain the problems faced by teachers in the context of learning. The method used is qualitative descriptive. The data collection techniques carried out include observation of the learning process, interviews with resource persons, and documentation to the subject concerned. The data collected is verified for validity by comparing the results of observations with the results of interviews. The data that has been collected is then analyzed with the stages of data management, data organization, and discovery of research results. The results of the study show two things: 1) efforts to improve students' ability and creativity in telling pictures using Indonesian by utilizing visual images that can be observed and told. 2) problems faced by teachers, especially related to students' difficulties in telling pictures due to limited vocabulary and the influence of everyday language. Therefore, the proposed solution is the application of learning approaches and strategies that suit the needs of students, so that learning can be more interesting and meaningful for them